2021
DOI: 10.18203/2394-6040.ijcmph20211974
|View full text |Cite
|
Sign up to set email alerts
|

Community attitude and practice towards skin disease prevention in a rural community in Busia County

Abstract: Background: Skin conditions were the fourth leading cause of nonfatal burden globally, expressed as years lost due to disability and eighteenth leading cause of health burden worldwide, expressed as disability adjusted life years. From Busia County health sector strategic and investment plan 2018-2023 report, skin diseases was third leading cause of morbidity in the county with 6.5%. Skin diseases, though very common in many developing countries, are not often regarded as a significant health problem even thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Descriptive study was adopted in Busia County, Kenya revealed that 68.4% had a hostile perception regarding skin conditions, and 45.9% of respondents believed that they may impede social and recreational activities, (38.1%) agreed that they would be affected if their partner or close friends or relatives had skin disease (Ogombo et al, 2021). A prevalence study was directed in Petaling district, Malaysia established that utmost of the respondents stayed cognizant of the hazard in fluencies of skin infection, 84.9% respondents knew that sharing their belongings known to be a risk factor, The discoveries exhibited that skin infection was correlated with causing problem with friends, relatives and partner (p-value<0.05) (Balakrishnan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive study was adopted in Busia County, Kenya revealed that 68.4% had a hostile perception regarding skin conditions, and 45.9% of respondents believed that they may impede social and recreational activities, (38.1%) agreed that they would be affected if their partner or close friends or relatives had skin disease (Ogombo et al, 2021). A prevalence study was directed in Petaling district, Malaysia established that utmost of the respondents stayed cognizant of the hazard in fluencies of skin infection, 84.9% respondents knew that sharing their belongings known to be a risk factor, The discoveries exhibited that skin infection was correlated with causing problem with friends, relatives and partner (p-value<0.05) (Balakrishnan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%